Novel Synthesized Tyrosinase Inhibitors: A Systematic Patent Review (2012-Present) - Beltran, Erika; Serafini, Mairim R.; Alves, Izabel Almeida; Aragón Novoa, Diana Marcela (Current Medicinal Chemistry, 2024)
Tyrosine is an enzyme responsible for melanin production. Its abnormal accumulation in different parts of the body is known as hyperpigmentation. Tyrosinase inhibitors have been used as one of the main approaches to treat these kinds of cosmetic and medical issues. This review aimed to discuss the advances in patents for this class of inhibitors, focusing on synthetic ones, by studying recent patent applications (2012-2022). We performed a screening using the European Patent Office’s Espacenet database, from which 15 inventions were selected and fully studied. China has more patent applications, all of them were focused on synthetic methods and the majority declared at least two additional applications as antibrowning agents for fruits and vegetables, biological pesticides, and medicine to treat diseases like Parkinson’s or melanoma. The strategies employed by the investigators focused on the examination of previous literature, which oriented on the type of structures that have been found to show good inhibitory activity; the study also examined aspects of their reaction mechanisms and information about the structureactivity relationship. For some groups of inhibitors, such as benzaldehyde and anthraquinone derivatives, the data were meaningful and extensive. In contrast, arginyl and troponoids compounds were difficult to analyze due to the limited research works.
Keywords: melanin